COX‐2 inhibition prevents the appearance of cutaneous squamous cell carcinomas accelerated by BRAF inhibitors. Issue 2 (1st December 2013) - Escuin-Ordinas, Helena; Atefi, Mohammad; Fu, Yong; Cass, Ashley; Ng, Charles; Huang, Rong Rong; Yashar, Sharona; Comin-Anduix, Begonya; Avramis, Earl; Cochran, Alistair J.; Marais, Richard; Lo, Roger S.; et al.
Abstract : Keratoacanthomas (KAs) and cutaneous squamous cell carcinomas (cuSCCs) develop in 15–30% of patients with BRAFV600E metastatic melanoma treated with BRAF inhibitors (BRAFi). These lesions resemble mouse skin tumors induced by the two‐stage DMBA/TPA skin carcinogenesis protocol; in this protocol BRAFi accelerates tumor induction. Since prior studies demonstrated cyclooxygenase 2 (COX‐2) is necessary for DMBA/TPA tumor induction, we hypothesized that COX‐2 inhibition might prevent BRAFi‐accelerated skin tumors. Celecoxib, a COX‐2 inhibitor, significantly delayed tumor acceleration by the BRAFi inhibitor PLX7420 and decreased tumor number by 90%. Tumor gene expression profiling demonstrated that celecoxib partially reversed the PLX4720‐induced gene signature. In PDV cuSCC cells, vemurafenib (a clinically approved BRAFi) increased ERK phosphorylation and soft agar colony formation; both responses were greatly decreased by celecoxib. In clinical trials trametinib, a MEK inhibitor (MEKi) increases BRAFi therapy efficacy in BRAFV600E melanomas and reduces BRAFi‐induced KA and cuSCC frequency. Trametinib also reduced vemurafenib‐induced PDV soft agar colonies, but less efficiently than celecoxib. The trametinb/celecoxib combination was more effective than either inhibitor alone. In conclusion, celecoxib suppressed both BRAFi‐accelerated skin tumors and soft‐agar colonies, warranting its testing as a chemopreventive agent for non‐melanoma skin lesions in patients treated with BRAFi alone or in combination with MEKi. Highlights: Celecoxib delays squamous cell carcinoma (SCC) tumor acceleration by PLX7420. It also decreases SCC tumor number by 90%. It partially reversed the PLX4720‐induced gene signature. Trametinb/celecoxib combination is more effective than either inhibitor alone.